The Meaning and Function of Pegon Inscriptions on The First Gate of Bejagung Lor Tomb Complex - Siti Nur Aqidatul Izza (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2024)
This study aims to examine the meaning and function of Pegon inscriptions on the first gate of the complex of Sunan Bejagung Lor's Tomb. The Pegon inscriptions are of significant size and contain advice or guidance. This qualitative research is based on a symbolic interactionism approach. Data is collected through interviews, field observations, and literature review. The research reveals that the Pegon inscriptions primarily serve as sengkalan for the numerals at the end of each sentence. They are also perceived as valuable advice by the local community, who view them as the wise words of the sunan. The gate was constructed in 1896 by Tuban regent, Raden Toemenggoeng Koesoemodikdo, not Sunan Bejagung's disciples. This research enriches our understanding of the history and culture of Sunan Bejagung Lor's Tomb and sheds light on the significance of the Pegon inscriptions on the gate.